2021
DOI: 10.33899/magrj.2021.127767.1059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biofertilizer Trichoderma Harzianum T-22 Application, Growing Medium and Training Methods on Some Chararctrestics for Lantana Camara Plants

Abstract: to investigate the effect of Trichoderma harzianum T-22 application and three growing media (soil, 1:3 soil: peatmoss, 1:1 soil: peatmoss) and three pruning training method (1, 4, 6 branches) and their interaction on the vegetative and flowering growth of Lantana camara. Results showed that T. harzianum application, the growing medium, pruning training method and their interaction had significant effects on the vegetative and flowering growth of plant. The highest average of plant height, stem diameter, leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…is known to promote growth, flowering, quality, and nutritional status of ornamental plants regardless of the substrate type [ 36 ]. An increase in the biomass and leaf area was observed in I. walleriana plants in our experimental conditions, as already found in tulip and gladiolus [ 37 , 38 ], polianthes [ 39 ], Lantana camara [ 40 ], begonia [ 41 ], sea lavender, cypress, and camellia [ 42 ] inoculated with different Trichoderma strains. Moreover, a significant effect on flowering performance attributable to the elongation of inflorescences and the development of flowers has been also demonstrated in tulip, polianthes, and begonia [ 38 , 39 , 41 ].…”
Section: Discussionsupporting
confidence: 85%
“…is known to promote growth, flowering, quality, and nutritional status of ornamental plants regardless of the substrate type [ 36 ]. An increase in the biomass and leaf area was observed in I. walleriana plants in our experimental conditions, as already found in tulip and gladiolus [ 37 , 38 ], polianthes [ 39 ], Lantana camara [ 40 ], begonia [ 41 ], sea lavender, cypress, and camellia [ 42 ] inoculated with different Trichoderma strains. Moreover, a significant effect on flowering performance attributable to the elongation of inflorescences and the development of flowers has been also demonstrated in tulip, polianthes, and begonia [ 38 , 39 , 41 ].…”
Section: Discussionsupporting
confidence: 85%
“…Have no impact on the number of leaves, but, depending on the fungus species used, they either stimulate or inhibit leaf blade elongation and influence its width [ 70 ]. Using T. harzianum T-22 in Lantana camara stimulates the elongation and thickening of shoots and the development of leaves [ 71 ]. Prisa [ 72 ], on the other hand, states that T. viride stimulates the elongation and formation of shoots and leaves, as well as the growth of the vegetative mass in plants of three species of the genus Kalanchoe ( K .…”
Section: The Impact Of Trichoderma Spp On the Qual...mentioning
confidence: 99%
“…The pruned plants of both varieties treated with the mycelium had the highest TSL. Yahya et al [40] observed a similar relationship in Lantana camara plants. The plants treated with T. harzianum and pruned most severely grew taller and had greater trunk diameters than those pruned less heavily and not inoculated.…”
Section: Growth and Flowering Of Plants After Application Of Trichode...mentioning
confidence: 72%